Is Being a Woman Enough? Towards Sonja Abadzhieva, Deep Breathing: Доволно ли е да си жена? Кон Соња Абаџиевa, Длабоко дишење - Bubevska, Aleksandra; Bushtrevska, Tamara (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Aleksandra Bubevska | Александра Бубевска Title (English): Is Being a Woman Enough? Towards Sonja Abadzhieva, Deep Breathing Title (Macedonian): Доволно ли е да си жена? Кон Соња Абаџиевa, Длабоко дишење Translated by (Macedonian to English): Tamara Bushtrevska | Тамара Буштревска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 232-235 Page Count: 4 Citation (English): Aleksandra Bubevska, “Is Being a Woman Enough? Towards Sonja Abadzhieva, Deep Breathing,” translated from the Macedonian by Tamara Bushtrevska, Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 232-235. Citation (Macedonian): Александра Бубевска, „Доволно ли е да си жена? Кон Соња Абаџиевa, Длабоко дишење“, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 232-235.